Subsurface geophysical profiling in Awash Melkesa: Insights into lithology and resource potential - Eyayu Ayalew Dessalew; Tilahun Mamo; Mohammed Yesuf Ali (PLoS ONE, 2025)
Integrated geophysical investigations were conducted around Awash Melkesa, located 106 km southeast of Addis Ababa, utilizing electrical resistivity, magnetic, radiometric, and seismic refraction methods. The geo-electric profile revealed five layers, with a notable low resistivity zone (113 Ohm-m) beneath VES 2, indicating a highly fractured and weathered ignimbrite, which suggests good potential for aquifers. The residual magnetic anomaly map varied from −312–296 nT, pointing to alluvial and pyroclastic sediments, while the tilt derivative magnetic map identified several faults oriented in N-S and NE-SW directions, consistent with the Wonji fault belt. Additionally, high concentrations of uranium and thorium were found in areas with felsic and intermediate extrusive igneous rocks, whereas lower concentrations were associated with weathered felsic rocks. The seismic velocity model identified three layers: the top layer, 3 m thick, showed P-wave velocities of 0.3–0.7 km/s; the second layer, at depths of 3–9 m, had velocities of 0.75–1.2 km/s, likely representing unconsolidated pyroclastic ignimbrite; and the third layer, between 9–18 m, exhibited a P-wave velocity of 2 km/s, indicating somewhat weathered and fractured ignimbrite. These findings provide valuable insights into the subsurface geophysical characteristics and potential resources in the Awash Melkesa area.